Opstanding in die boek Daniël - Nel, M (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
Resurrection in the Book of Daniel Daniel 12:1-3 refers to the resurrection but the exegesis of these verses is complicated and causes various problems for researchers. Questions arising out of the exegesis are: Does Daniel 12:1-3 teach a general resurrection, a resurrection for Israel, or a resurrection of a chosen group such as the martyrs from the Antiochan persecution? Is the resurrection tradition Israelite in origin or is it based on other religions and its traditions? Is resurrection defined as a life of eternal bliss and suffering for the righteous and evil respectively? Is it limited for a certain period? Is the image of resurrection related to individuals or to the corporate nation of Israel? In this article an exegesis of relevant themes in Daniel 12:1-3 is undertaken before a theological synthesis is given. The conclusion is that Daniel 12:1-3 contributes in various ways to Judaist thinking about the topic of resurrection, vindication of the righteous, and judgment of righteous and evil people.